Dalībvalstu tiesības ierobežot uzņēmuma pārcelšanos Eiropas Savienības ietvaros - Sergijenko, Anna (Latvijas Universitāte, 2009)
. The main goal of the study is to analyze how successfully the European Court of Justice has managed to find a way to secure that one of the fundamental freedoms – freedom of establishment – as regards the companies is put into practice at a minimum potential harm to the Member States. The discussions have risen wide in the light of the most recent Court decision in Cartesio case, where contrary to its former tendencies the Court decided not to allow the relocation of a central administration without the company being compulsory dissolved. The author finds out whether seeming “step back” in European integration is justified on the ground of overriding public interests in order to prevent dangerous tendencies developing, e.g. the race to the bottom – company mass migration to the state with the least onerous fiscal charges. Moreover, the Author evaluates the effect of the most recent developments in company relocation field.
The rights of the Member States to restrict relocation of companies within the European Union
Keywords: Juridiskā zinātne